Proceso de atención de enfermería en paciente de sexo femenino de 35 años de edad con trombosis venosa profunda. - Miranda Ortiz, Damaris Leonela (2019)
Deep vein thrombosis occurs most frequently in the third trimester of pregnancy and in the puerperium; due to changes in clotting factors that occur in pregnancy. The predisposing factors for women to have deep venous thrombosis are multiparity, advanced maternal age, obesity, a history of thromboembolism, not receiving the prophylactic dose of anticoagulants before cesarean delivery. The case of a woman with 5 days of a 35-year-old puerperium is presented, who went to the emergency service at the General Hospital Guasmo Sur with a clinical picture of two days of evolution at the time of the evaluation, presents edema in the lower extremity of the side left, difficulty walking, manifests pain, oriented in time and space, the control of vital signs presents, fever, hypertension and tachycardia, by assessment the doctor enters it with a presumptive diagnosis of deep vein thrombosis of the lower limbs and is indicated to perform Complementary exams to confirm the diagnosis.